ANALYSIS THE EFFECT OF POLITICAL CONNECTIONS AND OWNERSHIP STRUCTURE ON QUALITY CORPORATE GOVERNANCE - Ivone Ivone; Josna Josna (Universitas Internasional Batam, 2022)
The purpose of this study is to analyze the effect of quality corporate governance on political connections and ownership structures. In this research, quality corporate governance is measured by indicators. The independent variables used in this study are political connections, company size, leverage, diffuse ownership, and sales growth. The target of this research is companies listed on the Indonesia Stock Exchange, provided that they have an annual report from 2016 to 2020. The method used in this study is objective sampling, and the method used is panel data regression analysis. The conclusion of this study is that changes in company size, proliferation of ownership, and political ties have a significant positive impact on quality corporate governance.